Analisis Pengaruh Corporate Social Responsibility, Capital Intensity, Ukuran Perusahaan dan Profitabilitas Terhadap Tax Avoidance pada Perusahaan Sektor Energi - Lulu Devina Kalila; Dika Puspitaningrum (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2025)
This research investigates the impact of Corporate Social Responsibility (CSR), along with Capital Intensity, Firm Size, and Profitability, on practices of Tax Avoidance within energy firms registered on the Indonesia Stock Exchange (IDX) from 2022 to 2024. The matter of Tax Avoidance endures as a major concern, given its effects on government funds and business openness. By employing a quantitative method featuring a causal-associative structure, the study empirically explores the links between these factors. Information from secondary sources, including yearly reports and sustainability documents, was collected and examined through multiple linear regression analysis via IBM SPSS version 26. The findings show that CSR exerts a positive and meaningful influence on Tax Avoidance, whereas Capital Intensity and firm Size demonstrate positive influences that lack significance. In opposition, Profitability displays a negative and meaningful effect on Tax Avoidance. As a whole, the independent factors together exert a significant influence on Tax Avoidance behaviors. These outcomes strengthen agency and legitimacy theories, implying that CSR initiatives could function as a tool for securing legitimacy in handling tax duties while promoting long-term corporate adherence to fiscal obligations.